Efluente Anaeróbio Desinfetado com Ozônio/Peróxido de Hidrogênio - Da Silva, Gustavo Henrique Ribeiro [UNESP]; Daniel, Luiz Antonio; Contrera, Ronan Cleber; Bruning, Harry (My University, 2012)
This research aimed at studying the oxidation process, to verify the effectiveness of coliform inactivation and to evaluate the formation of ozonation disinfection byproducts (DBP) in anoxic sanitary wastewater treated with ozone/hydrogen peroxide applied at doses of 2.6 mg O3 L-1 and 2.0 mg H2O2 L-1 with contact time of 10 min and 8.1 mg O3 L-1 and 8.0 mg H2O2 L-1 with contact time of 20 min. The mean chemical oxygen demand (COD) reductions were 7.50 and 9.40% for applied dosages of 2.5 – 2.8 and 6.4 – 9.4 mg O3 L-1 + 2.0 and 8.0 mg H2O2.L-1, respectively. The Escherichia coli (E. coli) inactivation range was 2.98 – 4.04 log10 and the total coliform inactivation range was 2.77 – 4.01 log10. The aldehydes investigated were formaldehyde, acetaldehyde, glyoxal and methylglyoxal. It was observed only the formation of acetaldehyde that ranged 5.53 to 29.68 µg L-1
Anaerobic effluent disinfected with ozone/hydrogen peroxide
Keywords: Anaerobic effluent; Byproducts; Disinfection; Hydrogen peroxide; Ozone; Sanitary wastewater